International Regulatory and Scientific Effort for Improved Developmental Neurotoxicity Testing. (23rd November 2018) - Sachana, Magdalini; Bal-Price, Anna; Crofton, Kevin M; Bennekou, Susanne H; Shafer, Timothy J; Behl, Mamta; Terron, Andrea
Abstract: The Organisation for Economic Co-Operation and Development (OECD) coordinates international efforts to enhance developmental neurotoxicity (DNT) testing. In most regulatory sectors, including the ones dealing with pesticides and industrial chemicals registration, historical use of the in vivo DNT test guideline has been limited. Current challenges include a lack of DNT data and mechanistic information for thousands of chemicals, and difficulty in interpreting results. A series of workshops in the last decade has paved the way for a consensus among stakeholders that there is need for a DNT testing battery that relies on in vitro endpoints (proliferation, differentiation, synaptogenesis, etc.) and is complemented by alternative species (eg, zebrafish) assays. Preferably, a battery of in vitro and alternative assays should be anchored toward mechanistic relevance for applying an integrated approach for testing and assessment (IATA) framework. Specific activities have been initiated to facilitate this OECD project: the collation of available DNT in vitro methods and their scoring for readiness; the selection of these methods to form a DNT testing battery; the generation of a reference set of chemicals that will be tested using the battery; the case studies exemplifying how DNT in vitro data can be interpreted; and the development of an OECD guidance document. This manuscript highlights these international efforts and activities.